Expression of FUS‐CHOP fusion protein in immortalized/transformed human mesenchymal stem cells drives mixoid liposarcoma formation. (28th October 2013) - Rodriguez, Rene; Tornin, Juan; Suarez, Carlos; Astudillo, Aurora; Rubio, Ruth; Yauk, Carole; Williams, Andrew; Rosu‐Myles, Michael; Funes, Juan M.; Boshoff, Chris; Menendez, Pablo
Abstract : Increasing evidence supports that mesenchymal stromal/stem cells (MSCs) may represent the target cell for sarcoma development. Although different sarcomas have been modeled in mice upon expression of fusion oncogenes in MSCs, sarcomagenesis has not been successfully modeled in human MSCs (hMSCs). We report that FUS‐CHOP, a hallmark fusion gene in mixoid liposarcoma (MLS), has an instructive role in lineage commitment, and its expression in hMSC sequentially immortalized/transformed with up to five oncogenic hits (p53 and Rb deficiency, hTERT over‐expression, c‐myc stabilization, and H‐RAS v12 mutation) drives the formation of serially transplantable MLS. This is the first model of sarcoma based on the expression of a sarcoma‐associated fusion protein in hMSC, and allowed us to unravel the differentiation processes and signaling pathways altered in the MLS‐initiating cells. This study will contribute to test novel therapeutic approaches and constitutes a proof‐of‐concept to use hMSCs as target cell for modeling other fusion gene‐associated human sarcomas. Stem Cells 2013;31:2061–2072